The Efficacy of Crotalidae Polyvalent Immune Fab (Ovine) Antivenom Versus Placebo Plus Optional Rescue Therapy on Recovery From Copperhead Snake Envenomation: A Randomized, Double-Blind, Placebo-Controlled, Clinical Trial - Gerardo, Charles J.; Quackenbush, Eugenia; Lewis, Brandon; Rose, S. Rutherfoord; Greene, Spencer; Toschlog, Eric A.; Charlton, Nathan P.; Mullins, Michael E.; Schwartz, Richard; Denning, David; Sharma, Kapil; Kleinschmidt, Kurt; et al. (Annals of emergency medicine, 2017)
Copperhead snake (Agkistrodon contortrix) envenomation causes limb injury resulting in pain and disability. It is not known whether antivenom administration improves limb function. We determine whether administration of antivenom improves recovery from limb injury in patients envenomated by copperhead snakes. From August 2013 through November 2015, we performed a multicenter, randomized, double-blind, placebo-controlled, clinical trial to evaluate the effect of ovine Crotalidae polyvalent immune Fab (ovine) (CroFab; FabAV) antivenom therapy on recovery of limb function in patients with copperhead snake envenomation at 14 days postenvenomation. The study setting was 18 emergency departments in regions of the United States where copperhead snakes are endemic. Consecutive patients aged 12 years or older with mild- to moderate-severity envenomation received either FabAV or placebo. The primary outcome was limb function 14 days after envenomation, measured by the Patient-Specific Functional Scale. Additional outcomes included the Patient-Specific Functional Scale at other points; the Disorders of the Arm, Shoulder, and Hand, Lower Extremity Functional Scale, and Patient’s Global Impression of Change instruments; grip strength; walking speed; quality of life (Patient-Reported Outcomes Measurement Information System Physical Fucntion-10); pain; and analgesic use. Seventy-four patients received study drug (45 FabAV, 29 placebo). Mean age was 43 years (range 12 to 86 years). Fifty-three percent were men, 62% had lower extremity envenomation, and 88% had mild initial severity. The primary outcome, the least square mean Patient-Specific Functional Scale score at 14 days postenvenomation, was 8.6 for FabAV-treated subjects and 7.4 for placebo recipients (difference 1.2; 95% confidence interval 0.1 to 2.3; P=.04). Additional outcome assessments generally favored FabAV. More FabAV-treated subjects experienced treatment-emergent adverse events (56% versus 28%), but few were serious (1 in each group). Treatment with FabAV reduces limb disability measured by the Patient-Specific Functional Scale 14 days after copperhead envenomation.